Ultra-Small One-Dimensional Rice-Like comoo4 Nanorods as a Promising Pseudocapacitive Electrode for High-Performance Supercapacitors - Radhalayam, D (Elsevier Ltd, 2025)
The demand for sustainable energy sources increases as society progresses. Supercapacitors possess a long lifespan, have a high power density, are ecologically sound, and have the ability to rapidly charge and discharge. Among the several binary transition metal oxides (BTMOs), metal molybdates (AMoO4) are notable for their significant redox activity, widespread availability, affordability, and small ecological footprint. The exceptional theoretical capacitance of CoMoO4, resulting from the presence of active cobalt ions, distinguishes it from other materials. However, the synthesis of CoMoO4 in nanostructured forms presents a challenge. This study introduces a straightforward one-pot solvothermal technique for producing ultra-small, one-dimensional (1D) rice-like CoMoO4 nanorods. The electrochemical performance of rice-like CoMoO4 nanorods as a supercapacitor electrode material was thoroughly investigated, along with larger CoMoO4 nanorods made using the hydrothermal process for comparison. The structural, morphological, and surface characteristics of the rice-like CoMoO4 nanorods were comprehensively examined. The nanorods, formed like rice grains, exhibited exceptional ability to store electric charge, with an outstanding specific capacitance of 1608.8 F g−1. They demonstrated remarkable cycling stability, retaining 96 % of their capacitance after numerous charge and discharge cycles, indicating their durability and reliability. The nanorods also exhibited a high rate capability of 71 %, which is crucial for applications that demand quick energy delivery. This capability enables the nanorods to maintain considerable capacitance even at higher charge-discharge rates. The results indicate that rice-like CoMoO4 nanorods can be used as a material in supercapacitors. © 2024 Elsevier Ltd
Keywords: CoMoO4 nanorods; X-ray powder diffraction; Electrochemical performance; Specific capacitance; Supercapacitors